Estimands - a basic element for clinical trials: part 29 of a series on evaluation of scientific publications - Pohl, Moritz; Baumann, Lukas; Behnisch, Rouven; Kirchner, Marietta; Krisam, Johannes; Sander, Anja (Deutsches Ärzteblatt, 2021)
Clinical trials represent one of the cornerstones of evidence-based medicine and are intended to investigate a medical question of interest, the answer to which is formulated as a trial objective. For a trial in which a new drug to treat type-2...